Essentials of nursing leadership & management - Weiss, Sally A., 1950-; Tappen, Ruth M.; Grimley, Karen A. (Philadelphia, PA : F.A. Davis Company, 2024)
'We are pleased to bring our readers this eighth edition of Essentials of Nursing Leadership & Management. This new edition has been updated to reflect the dynamic health-care environment, new safety and quality initiatives, diversity, lessons learned during the pandemic , changes in the nursing workforce and transformations in the nursing practice environment. This edition focuses on essential leadership and management skills and the knowledge needed by the staff nurse as a key member of the interprofessional health-care team and manager of patient care. Issues related to setting priorities, delegation, quality improvement, legal parameters of nursing practice, and ethical issues were also updated for this edition'--
Characteristics of a profession -- Professional ethics and values -- Nursing practice and the law -- Leadership and followership -- The nurse as manager of care -- Delegation and prioritization of client care staffing -- Communicating with others and working with the interprofessional team -- Resolving problems and conflicts -- Organizations, power, and professional empowerment -- Organizations, people, and change -- Quality and safety -- Maintaining a safe work environment -- Promoting a healthy work environment -- Launching your career -- Advancing your career -- What the future holds.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 22, 2023).
OCLC control number change
Keywords: Nursing services -- Administration; Leadership; Leadership; Nursing, Supervisory; Nursing Services -- organization & administration; United States; Services infirmiers -- Administration; Leadership